2020
DOI: 10.1352/1944-7558-125.3.170
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and the Reciprocal Nature of Family Relationships: The Perspective of Individuals With Mild Intellectual Disability

Abstract: Even though family plays a significant role in the lives of people with intellectual disability, little research has included their own views about their families. This study examined how 138 people with mild intellectual disability describe their family group, with a focus on the reciprocal nature of the emotional support in relationships with family members. Participants reported “significant” family members beyond the nuclear family, and parents were seen as the main provider of support. Only half of partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 48 publications
0
17
1
Order By: Relevance
“…2019; Giesbers et al . 2020). Free recall techniques of network data have generally shown good scores of reliability and validity (Ferligoj and Hlebec 1999), and the original FNM has demonstrated test–retest reliability (Monney 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2019; Giesbers et al . 2020). Free recall techniques of network data have generally shown good scores of reliability and validity (Ferligoj and Hlebec 1999), and the original FNM has demonstrated test–retest reliability (Monney 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Ethical approval was obtained from the Ethical Review Board of Tilburg University (EC‐2015.46) The 53 participants with mild intellectual disability were part of a larger sample of 150 individuals with mild intellectual disability aged 18–40 years (Giesbers et al . 2020). For the current study, they were selected from the larger sample based on the criterion that they were aged between 18 and 25 years as a match with the student sample in the emerging adulthood period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our explorative studies provide valuable insights into the experiences and needs of people with an intellectual disability, their mothers, and care professionals during the COVID-19 pandemic in the Netherlands and relate to the key role of social supportive networks in the lives of people with an intellectual disability. Earlier research found social supportive networks of people with intellectual disabilities to be relatively small (e.g., van Asselt-Goverts et al 2013), and families, and especially parents, often proved to be the main provider of informal support to people with an intellectual disability (e.g., Giesbers et al 2020). Professionals also play a key role in the support of people with intellectual disabilities, which is not only the case for people with intellectual disabilities living in more segregated residential facilities but also for those receiving community-based residential support or living independently in the community.…”
Section: Supportive Relationshipsmentioning
confidence: 99%
“…Initial results using the FNM-ID showed that there is likely to be considerable variation in the perceived family networks of people with intellectual disabilities, in terms of size and (reciprocal) emotional support (Giesbers et al, 2020). Examining family typologies can have practical implications, as different types of families might require different professional support.…”
mentioning
confidence: 99%